Leishmania spp. and/or Trypanosoma cruzi diagnosis in dogs from endemic and nonendemic areas for canine visceral leishmaniasis - Troncarelli, Marcella Zampoli [UNESP]; Camargo, Janaina Biotto [UNESP]; Machado, Juliana Giantomassi [UNESP]; Lucheis, Simone Baldini [UNESP]; Langoni, Hélio [UNESP] (Elsevier B.V., 2009)
Due to the phylogenetic similarity between Leishmania spp. and Trypanosoma cruzi (T cruzi), serological cross-reactions and false-positive results are quite common. This study aimed to elucidate canine leishmaniasis and trypanosomiasis diagnosis by the indirect fluorescent antibody test (IFAT) on serum samples, and direct parasitological examination and polymerase chain reaction (PCR) in liver and spleen samples. One hundred dogs from Zoonosis Control Center (ZCC) in Bauru, SP, an endemic area for visceral leishmaniasis (VL), and 100 dogs from the Dog Warden Service in Botucatu, SP, a nonendemic area for VL, were studied. IFAT showed positive results for Leishmania spp. in 65% of canine serum samples from Bauru while 40% of the samples were positive for T cruzi by this test. All samples from Botucatu were negative for leishmaniasis in IFAT, and only 4% were positive for T cruzi. Out of 200 serum samples tested, 33 (16.5%) showed positive serological results for both the parasites. Direct parasitological examination and PCR found, respectively, 59% and 76% of the liver samples and 51% and 72% of the spleen samples of dogs from Bauru positive for Leishmania spp. Twenty-six (78.8%) of 33 dogs that showed anti-Leishmania spp. and anti-T cruzi antibodies also tested positive by direct parasitological examination and PCR for Leishmania spp., which indicates that these dogs presented leishmaniasis. No liver or spleen sample from the 200 dogs analyzed showed a positive PCR result for T cruzi. These findings support the occurrence of cross-reactions between Leishmania spp. and T cruzi in IFAT; they also corroborate the need for simultaneous PCR and/or parasitological examination to establish canine leishmaniasis (CL) diagnosis. (C) 2009 Elsevier B.V. All rights reserved.
Keywords: Leishmania spp.; Trypanosoma cruzi; Diagnosis; Dog